ANALISIS KINERJA USAHA DAN RISIKO PETAMBAK UDANG VANAME PADA SISTEM TRADISIONAL DAN SISTEM SEMI INTENSIFDI KECAMATAN LABUHAN MARINGGAI KABUPATEN LAMPUNG TIMUR - Dewi Sartika Putri; Muhammad Irfan Affandi; Wuryaningsih Dwi Sayekti (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This study aims to analyse the farm performances and the risk of vaname shrimp farmers in conventional and semi-intensive technology in Labuhan Maringgai Subdistrict, East Lampung Regency with the consideration that the location was vaname shrimp production center. The sample in this study were 35 vaname shrimp farmers consisting of 24 conventional farmers and 11 semi-intensive farmers that were randomly selected disproportionately. The research data were collected in March 2019 and analysed using quantitative analysis of farm performance and production risk. The results showed that the farm performance of conventional vaname shrimp farming tended to be better than of the semi-intensive farming.  Production risk of conventional vaname shrimp farmers has a higher chance of loss or production risk compared to semi-intensive shrimp farmers.Key words: farm performance, risk, vaname shrimp